Maslahah-mafsadah approach on Muslim travel decision-making (MTDM) - Saffinee, Siti Syahirah Saffinee; Hashim, Khairusy Syakirin Has-Yun; Jamaludin, Mohammad Aizat; Othman, Rashidi (2018)
Maslahah-Mafsadah concepts emerge in Islamic tourism to promote a particular undertaking to understand the Maqasid Shariah discourse. Scholars’ contribution in this subject is lacking particularly in the determination of challenges in Muslim travel decision-making (MTDM). A decision-making style here refers to the struggle of the Muslim traveler to overcome the obstacles that keep them from God (jihad) by practicing highest moral standards (fasting) and consistently being obedient-servant to what they do when making travel choices. This article aims to determine the Maslahah-Mafsadah concept by integrating it into MTDM. In doing so, this article first presents the philosophy of Maslahah-Mafsadah as well as Maqasid Shariah; secondly, it explores the concept of integration to MTDM on selecting a destination, travel guide, accommodation and halal food; finally, it formulates a standard for it in light of these applications for travelers.